IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SQ5R METHODS: A DISTANCE LEARNING DURING THE PANDEMIC COVID-19 - M. Labib Al Halim (Jurnal Bahasa Lingua Scientia, 2023)
The entry of the Covid-19 virus in Indonesia has had a major impact on the education sector. The teacher could use several strategies during the learning process to be able to achieve the learning objectives. This study aimed to optimize the use of the Survey, Question, Read, Recite, Record, Review, Reflect (SQ5R) method in teaching reading during online learning at SMPN 3 Lamongan. The researcher used action research with direct observation during the learning process. The results showed that the SQ5R method could improve students' reading comprehension. The minimum score obtained by students in the initial test was 45. This value increased up to 65 in the final test, which indicated that all students had reached the minimum passing criteria standard that had been set. Meanwhile, the observations showed that students were able to analyze visual information, predict content and improve their notes. Overall, it was evident that the SQ5R approach has a positive impact on students' reading comprehension.